Supervisi Oleh Komisi Pemberantasan Korupsi Dalam Pengambilalihan Perkara - Reunussa, Mahalia; Salmon, Hendrik; Titahelu, Juanrico Alfaromona Sumarezs (MATAKAO Corruption Law Review, 2024)
Introduction: Supervision is an activity of supervision, research or review of agencies authorized to carry out the eradication of criminal acts of corruption in order to accelerate the resolution of the handling of a case. Purposes of the Research: This research aims to analyze the law enforcement process related to the takeover of cases by the Corruption Eradication Commission against Police and Prosecutor's Offices that handle criminal acts of corruption that do not comply with the procedures in the law. Methods of the Research: Method used Normative legal research, research approaches, namely the statutory approach, conceptual approach and case approach. Results of the Research: The results of the research explain that in the context of law enforcement in taking over corruption cases, the procedures in Article 10A of Law no. 19 of 2019, an important process is needed, namely the Judicial Administrative Procedure, to control the performance of investigators to avoid legal irregularities.